Answer:
[tex]x=1\,,\,y=-1[/tex]
Step-by-step explanation:
Given: [tex]ax+by=a-b\,,\,bx-ay=a+b[/tex]
To solve: the given linear equations
Solution:
Consider the equations:
[tex]A_1x+B_1y+C_1=0\\A_2x+B_2y+C_2=0[/tex]
By method of cross multiplication:
[tex]\frac{x}{B_1C_2-B_2C_1}=\frac{y}{C_1A_2-C_2A_1}=\frac{1}{A_1B_2-A_2B_1}[/tex]
For equations: [tex]ax+by=a-b\,,\,bx-ay=a+b[/tex]
[tex]ax+by-(a-b)=0\\bx-ay-(a+b)=0[/tex]
Take [tex]A_1=a\,,\,B_1=b\,,\,C_1=-(a-b)\,,\,A_2=b\,,\,B_2=-a\,,\,C_2=-(a+b)[/tex]
So,
[tex]\frac{x}{-b(a+b)-a(a-b)}=\frac{y}{-b(a-b)+a(a+b)}=\frac{1}{-a^2-b^2}\\\frac{x}{-ab-b^2-a^2+ab}=\frac{y}{-ab+b^2+a^2+ab}=\frac{1}{-(a^2+b^2)}\\\frac{x}{-(a^2+b^2)}=\frac{y}{a^2+b^2}=\frac{1}{-(a^2+b^2)}\\\frac{x}{-(a^2+b^2)}=\frac{1}{-(a^2+b^2)}\,,\,\frac{y}{a^2+b^2}=\frac{1}{-(a^2+b^2)}\\x=1\,,\,y=-1[/tex]